PENGARUH PROSES CURING BUAH TAKOKAK (Solanum torvum) SELAMA PENYIMPANAN SUHU RUANG 5 HARI TERHADAP KADAR PROKSIMAT DAN SUSUT BOBOT - Nunuk Helilusiatiningsih (Journal of Food Technology and Agroindustry, 2022)
Takokak plants are often called eggplant pokak or eggplant sparrows can grow in a moist, fertile and shaded area and are popular abroad under the name turkey berry. The problem is that this plant is still relatively few who consume and cultivate it. The research objective was to study the effect of takokak curing treatment on proximate components and weight loss during 5 days room temperature storage. The method used is the proximate compound test and quantitative weight loss with valid analytical procedures. The test parameters include water content, ash content, protein, fat, carbohydrates and weight loss. Chemical analysis results for 5 days of curing are: Water content (%) : 81.72 ; 79, 24; 77.16 ; 75.42 ; 72.31. Ash content (%): 1.63 ; 1.72; 1.98; 2.15; 2.24. Protein (%): 9.28 ; 8.47; 7.91; 6.98; 5.76. Fat (%): 2.65; 2.51; 2.38; 2.24; 2.18. Carbohydrates (%): 5.36 ; 7.21; 9.53; 11.20; 13.36. Weight Loss (grams): 5.68; 5.12; 4.84 ; 4.41; 4.08.